The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4md00177j
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, synthesis and NMR characterization of novel chimera compounds targeting STAT3

Abstract: Chimera derivatives as potential STAT3 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This model was used to screen a database of 78 compounds and the four highest-scoring compounds and a negative control were tested. Among them, compound (73) (Fig. (13)) was the most potent derivative, satisfying all the features of the pharmacophore model [ 46].…”
Section: Non-peptidic Compoundsmentioning
confidence: 79%
See 2 more Smart Citations
“…This model was used to screen a database of 78 compounds and the four highest-scoring compounds and a negative control were tested. Among them, compound (73) (Fig. (13)) was the most potent derivative, satisfying all the features of the pharmacophore model [ 46].…”
Section: Non-peptidic Compoundsmentioning
confidence: 79%
“…(13)) was the most potent derivative, satisfying all the features of the pharmacophore model [ 46]. A molecular docking analysis of compound (73) with STAT1 and STAT5 demonstrated that this compound is able to bind to both of them with unfavorable binding scores. A STAT3 DNA-binding assay was performed to examine the effect of the hit compound on DNA-binding activity, treating nuclear extracts from EGF-stimulated cells with the new compound and S3I-201 (74) (a known STAT3 inhibitor, Fig.…”
Section: Non-peptidic Compoundsmentioning
confidence: 89%
See 1 more Smart Citation
“…We have also shown that these novel pyrrolo[3,4- d ]pyridazinone derivatives can alleviate inflammatory response in the carrageenan-evoked inflammation model and their mechanism of action might be related to the decrease in the PGE 2 , TNF-α, and MPO levels and the reduction in inflammatory cell infiltration in inflamed tissues [ 20 ]. Several other studies have indicated that compounds based on both pyridazinone [ 21 ] and 1,3,4-oxadiazole [ 22 , 23 , 24 ] scaffolds are able to interfere with the STAT3 pathway, which is involved in Th17 cells differentiation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 1, 3, 4-oxadiazole scaffold is extensively used in the inhibition of STAT3 in various cancer cells. Dell'Orto et al [22] showed that an oxadiazole based compound effectively inhibited the activation of STAT3 by targeting the STAT3-SH2 domain in a dose-dependent manner. Shin et al [23] reported that oxadiazoles containing ureido derivatives inhibited STAT3 signaling by blocking the upstream tyrosine kinases involved in the activation of STAT3.…”
Section: Introductionmentioning
confidence: 99%